Product design specifications: force plates for rowing - Kulkarni, N.; Kaur, S.; Wadzinski, E.; Topercer, B.; Ryan, O.; Bhatia, S. (University of Wisconsin-Madison, 2023)
Force sensors have been widely used in sports biomechanics to measure load distribution and center of pressure for the purpose of correcting form and mitigating injuries. However, getting this real time data is often difficult to obtain in non clinical settings and may be very expensive to implement. Rowing is a rigorous sport that can lead to numerous lower extremity injuries due to asymmetries in load distribution when not following proper technique. Additionally, this asymmetry is impossible to quantify visually and can only be considered from stationary rowing simulation machines that disparately underestimate the mechanical power required against water currents [1]. Current methods of analyzing lower extremities from rowing include isolated studies that measure degree of leaning towards one side but not force loading. Our design aims to provide more accurate data by integrating a force sensor system in the rowboat to transduce real time data that rowers can view while on the water. The application of our design will allow athletes and coaches to gain greater insight into performance enhancement and injury prevention.